2007
DOI: 10.1248/bpb.30.1934
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Water Containing Magnesium Ion on Paw Edema in Adjuvant-Induced Arthritis Rat

Abstract: ᭹, AA rats administered IM (2 mg/kg) and PW; ᭺, AA rats administered IM (2 mg/kg) and BW-5. The data are presented as meansϮS.E. of 5 independent rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Recently, we reported that the oral administration of Mg 2+ to AA rats prevents the development of inflammation, 27) and that the co-administration of Mg 2+ and indomethacin suppresses hemorrhagic lesions in the gastric mucosa of AA rats. 24) In this study, we investigated the preventive effect of water containing Mg 2+ on loxoprofen-induced gastric lesions in AA rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that the oral administration of Mg 2+ to AA rats prevents the development of inflammation, 27) and that the co-administration of Mg 2+ and indomethacin suppresses hemorrhagic lesions in the gastric mucosa of AA rats. 24) In this study, we investigated the preventive effect of water containing Mg 2+ on loxoprofen-induced gastric lesions in AA rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we previously reported that the co-administration of Mg 2+ does not affect the plasma IMC concentration. 17) These results show that MW can suppress the onset of the IMC-induced intestinal ulcers.…”
Section: 4)mentioning
confidence: 72%
“…Our previous reports showed that the oral administration of Mg 2+ to AA rats prevents the development of inflammation, and the combination of IMC and Mg 2+ provide an effective therapy of arthritic edema. 17) Therefore, these findings provide significant information that can be used to design further studies to develop potent NSAIDs that do not cause gastrointestinal toxicity.…”
Section: +mentioning
confidence: 94%
“…The joint diameter and functional parameters given below were scored before injecting FCA, daily for first 3 days and then every alternate day till day 16, a time when these scores normalized in arthritic control. A time-course for increase in joint diameter from day 0 values was plotted and the area under doi: 10.7243/2054-720X-1-1 curve (AUC) as an index of inflammation was determined [5]. The animals were sacrificed on day 16, joint tissue dissected out and stored at -80 o C for biochemical analysis.…”
Section: Following Groups (N=6) Were Includedmentioning
confidence: 99%